Towards equitable commissioning for our multiethnic society : a mixed-methods qualitative investigation of evidence utilisation by strategic commissioners and public health managers /: a mixed-methods qualitative investigation of evidence utilisation by strategic commissioners and public health managers. (December 2013) - Salway, Sarah, 1966-
No abstract available